Transformation And Management Strategy Human Resources : Managing Adaptation Employees And Development Skills In The Industrial Era 4.0 - Muhammad Raihan; Aprinawati, Aprinawati; Mhd. Fadillah Ilham Sinaga; Muhammad Lintar Kodratullah; Nada Deliza Putri; Putra Jhonatan Mula Jaya Napitupulu; Reni Marlina Sianturi; T Rendy Julian (Jurnal Multidisiplin Sahombu, 2024)
Digital transformation in the Industry 4.0 era brings major challenges for organizations , especially in managing human resources (HR) who must adapt to new technologies . This study aims to explore HR strategies that can support the digital transformation process in Indonesian organizations , with a focus on managing employee adaptation and developing skills to face rapid technological changes . This study uses a descriptive qualitative approach through a literature study, which collect information from various references related to previous theories and research . The results of the study indicates that the success of digital transformation is highly dependent on an integrated and adaptive HR strategy . Organizations need to manage resistance to technological change by providing skills training ( upskilling) and reskilling ), creating a supportive work environment , and strengthening employees ' technical and non- technical skills . In addition , transparent communication and inclusive leadership is essential to facilitate the employee adaptation process . This study concludes that with proper HR management , organizations can create a workforce that is ready to face challenges in the digital era and ensure business sustainability in the future .